Development and validation of a simple method for the determination of triamcinolone acetonide in nasal spray - Haya S. Alzeer; Shikah F. Alzaid; Fahad S. Aldawsari; Yahya M. Alshehri (Elsevier, 2023)
A rapid, convenient, and sensitive analytical technique for quantitative analysis of triamcinolone acetonide (TAC) in pharmaceutical nasal spray dosage form using the blue tetrazolium colorimetric reaction and UV spectrophotometric method was developed and validated. Beer's law of the developed method was proven in the concentration range of 10-40 µg/mL and showed a specific linear relationship with coefficient value R2 = 0.998. The LOQ level was 9.99 µg/mL, with (RSD = 0.26%). From precision assay, RSD values have been obtained for the repeatability and intermediate precision, which were found to be (RSD = 1.65%) and (RSD = 2.01%), respectively, indicating that the method is reproducible. Recovery studies showed mean recoveries in the range of (100.08-103.65 %), meeting the acceptance criteria for accuracy. In addition, we compared the results of the developed method UV-Vis spectrophotometric procedure with those of a well-established official USP analytical procedure (HPLC), and the results showed good agreement. The proposed UV method represents a potential alternative to the official USP analytical assay procedure (HPLC) for estimating TAC in nasal spray forms. Furthermore, it has the potential to be implemented in routine use for rapid qualitative and quantitative determinations for TAC.